The PLA’s Role in China’s Regional Security Strategy - Qi, Dapeng (2016)
National development has gradually replaced national survival as the focus of China’s national security strategy. Accordingly, the PLA has been assigned the new mission of ensuring China’s development interests. Compared to the emphasis on the means of military confrontation and conflict in safeguarding China’s national survival in the past, the PLA’s new mission emphasizes the strengthening of military confidence building and regional security cooperation with others. Over the past 15 years, the PLA has played a role in shaping a security environment for peaceful development, which has focused mainly on three tasks: (i) building military trust with its neighbouring counterparts; (ii) participating in regional security cooperation processes; and (iii) improving its ties with the United States and other players. At the same time, there are several factors that pose challenges to the PLA’s success in its new mission, including: (i) mutual apprehension between China and its neighbours; (ii) strategic suspicions between China and the United States; and (iii) the potential Japan-China rivalry. This paper concludes with a discussion on how the PLA can carry out its mission while managing these potential challenges at the same time.